Overlooked intersection of gender and racial/ethnic dimensions in Slovenian academic sexual harassment & violence policies - Dežan, Lucija (Annales. Series historia et sociologia, 2024)
This article addresses the need to adopt an intersectional perspective when discussing sexual harassment and violence in academia. The introduction of an intersectional perspective is important since sexual harassment and violence in relation to racial and ethnic minorities seldom revolve exclusively around gender. Recognising the intersectional nature of sexual assault and harassment means also recognising the coexistence of racism and nationalism, the perpetuation of ethnic/racial stereotypes, the multifaceted manifestations of discrimination, and a matrix of domination that exists in our society and educational and research institutions as well. In this article, we analysed official documents of Slovenian higher education and research institutions (public and private ones) with an aim to examine whether and how they address intersectionality and racial/ethnic minorities in their policies combating sexual harassment and violence. The results revealed a significant ignorance towards intersectionality of gender and ethnicity, but also issues arising from accessibility of these policies.
Keywords: "rasa"; “race”; “razza”; ethnicity; etnia; etničnost; gender; genere; intersectionality; intersekcionalnost; intersezionalita; istituti di ricerca; molestie e violenze sessuali; research institutions; sexual harassment and violence; spol; Spolno nadlegovanje; spolno nadlegovanje in nasilje; universita; university; univerza; Višje in visoke šole